PENGARUH CURRENT RATIO DAN DEBT TO EQUITY RATIO TERHADAP LABA PADA PT. ASTRA INTERNATIONAL Tbk SELAMA PERIODE 2006 – 2015 - Saiyid Syekh; Anisah Anisah (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2017)
Current Ratio is one of the company's ability to pay its short-term liabilities with its assets. Debt to Equity Ratio is the ability of the company to fulfill all its obligations, indicated by what part of the capital itself used to pay the debt. Profit is an indicator of achievement or performance of a company whose magnitude appears in the financial statements, exactly profit and loss. The objective of this research is to know whether there is influence between Current Ratio and Debt to Equity Ratio and more dominant variable between both variables at PT.Astra International registered in BEI period 2006-2015. PT.Astra International is a multinational company that produces automotive and which is produced from automotive itself that is car, sepedamotor and spare parts and also distribute heavy equipment. Which is headquartered in Jakarta, Indonesia. It is known that F count is 24,646 by comparing F table α = 0,05. And on the t test results can be known to Debt to Equity Ratio has t count of 2.239 while ttable of 2.36 so t count < t table with a significant probability to variable Debt to Equity Ratio of 0.002 smaller than at a significant level of 0.05 can be concluded that the partial Current Ratio effect Significantly and positively to Net Income.Keyword: current ratio, debt to equity ratio